Long term outcomes in 46, XX adult patients with congenital adrenal hyperplasia reared as males. Issue 165 (January 2017) - Khattab, A.; Yau, M.; Qamar, A.; Gangishetti, P.; Barhen, A.; Al-Malki, S.; Mistry, H.; Anthony, W.; Toralles, M.B; New, Maria I.
Abstract: Patients with Congenital Adrenal Hyperplasia (CAH) owing to 21-hydroxylase deficiency and whose karyotype is 46, XX are usually assigned to the female gender. Reported herein are the long term outcomes in three patients with CAH whose karyotype is 46, XX and who were reared as males. A retrospective review of three CAH patients with a 46, XX karyotype who were reared as males was conducted. Gender assignment, clinical and biochemical data, pre and post-genitoplasty genital examinations were reviewed. Gender identity was tested by an extensive questionnaire. Gender role, sexual preference, marital status and sexual satisfaction were evaluated by interview. The three patients were genotyped for the CYP21A2 gene confirming the diagnosis of CAH. Owing to genital virilization, cultural preferences for male gender and the lack of newborn screening programs the three patients reported herein were assigned to the male gender at birth before the diagnosis of CAH was established. In adulthood the patients remained significantly virilized. Thorough psychosexual assessments in adulthood revealed well established male gender identities compatible with their male gender assignments at birth. In all three patients, gender role and behavior were consistent with male gender identity including sexual intercourse with female partners. The three patients reported herein revealed that male gender assignment to CAH patients with a 46, XX karyotype may have a successful outcome providing there is strong parental support and expert endocrine care. No standard guidelines have been published for the gender assignment of CAH patients with a 46, XX karyotype and genital ambiguity. More studies concerning gender assignment in CAH patients with a 46, XX karyotype reared as males are needed.